PENGARUH AROMATERAPI LAVENDER TERHADAPPENGURANGAN NYERI PERSALINAN KALA I AKTIF - Evi Nira Hetia; M. Ridwan; Herlina Herlina (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2017)
Labor Pain is caused by uterine contractions through increased secretion of catecholamine and cortisol levels, leading to a decrease in uterine blood flow and decreased uterine activity that will result in prolonged labor. Lampung Province has one maternal mortality case caused by prolonged-labor. The incidence of prolonged labor at midwife private practice Opsi Okta HN in June was 20% (2 cases), July was 27% (3 cases), and in August was 20% (2 cases). Lavender aromatherapy is one of the non-pharmacological useful methods to reduce the pain, relax the mind, reduce tension and anxiety and give peace to the maternity mother. This study aims to determine the influence of lavender aromatherapy on the reduction of labor pain during the active phase I. This study was conducted with the experimental design of the final and post test group. The sample technique used purposive sampling on 15 people. The collection of pain data using the scale of assessment of pain and lavender aromatherapy with the observational method. The univariate analysis of data using mean and bivariate analysis with parametric statistical test dependent Paired t Test.The result of the average intensity of pain in maternal mothers before given lavender aromatherapy was 7.07 (Pain Weight) and after given lavender aromatherapy was 5.53 (moderate pain). The result of Paired t Test is obtained p value 0,000 (p α 0,05).The Conclusion of the research is the influence of lavender aromatherapy on the reduction of labor pain during the active phase I. It is expected that midwives can apply lavender aromatherapy and non-pharmacological practical method as an alternative in reducing labor pain.